Celiac Disease Frequency Is Increased in IgE-Mediated Food Allergy and Could Affect Allergy Severity and Resolution. Issue 1 (29th January 2023) - Lega, Sara; Badina, Laura; De Leo, Luigina; Andrade, Stefanny; Ziberna, Fabiana; Gaita, Bartolomea; Di Leo, Grazia; Bramuzzo, Matteo; Barbi, Egidio; Not, Tarcisio; Berti, Irene
Abstract : Objectives: An increased frequency of celiac disease (CeD) has been reported in severe Immunoglobulin E (IgE) -mediated food allergy (FA). This observation requires confirmation, and whether CeD affects FA severity and resolution is unknown. The study aims to estimate the prevalence of CeD in patients with FA and to investigate whether CeD affects FA severity and oral tolerance. Methods: Consecutive patients with FA referred for allergen reintroduction, either to evaluate allergy resolution or to start oral immunotherapy (OIT), were evaluated for CeD and for FA severity. The primary outcome was the prevalence of CeD. Secondary outcomes were the frequency of severe FA and the level of clinical tolerance at study entry and at last follow-up in patients with isolated FA versus patients with FA + CeD. Results: Two hundred twenty-eight patients were included. CeD was confirmed in 15 patients (6.6%) of whom, 8 patients had a previously established diagnosis of CeD and were on a gluten-free diet. Severe FA was observed in 12 patients with FA + CeD (80%) versus 88 patients with FA (42%) ( P = 0.006). At baseline, patients with FA + CeD had significantly higher median allergen-specific IgE levels [61.8 kU/L; interquartile range (IQR) 11.6–279.0] compared to patients with FA (20.3 kU/L; IQR 2.9–72.7) ( P < 0.001). Complete clinical tolerance was observed in 1 of 15 patients (7%) with FA + CeD versus 98 of 205 patients (48%) with FA ( P = 0.002). Conclusions: CeD is highly prevalent in patients with FA and could affect FA severity and response to OIT. CeD screening should be considered in patients with severe or persistent FA.